Drawing on the Victorians The Palimpsest of Victorian and Neo-Victorian Graphic Texts - Jones, Anna; Mitchell, Rebecca (Ohio University Press, 2015)
Late 19th-century Britain experienced an explosion of visual print culture and a simultaneous rise in literacy across social classes. New printing technologies facilitated quick and cheap dissemination of images-illustrated books, periodicals, cartoons, comics, and ephemera-to a mass readership. This Victorian visual turn prefigured the present-day impact of the Internet on how images are produced and shared, both driving and reflecting the visual culture of its time. From this starting point, Drawing on the Victorians explores the relationship between Victorian graphic texts and today's steampunk, manga, and other neo-Victorian genres that emulate and reinterpret their predecessors. Neo-Victorianism is a flourishing worldwide phenomenon, but one whose relationship with the texts from which it takes its inspiration remains underexplored.